Dynamic Response of Ductile Materials from Split Hopkinson Tension Bar Tests - Partom, Yehuda; Lindenfeld, A. (European Journal of Applied Sciences, 2023)
We use a SHTB (= Split Hopkinson Tension Bar) system to test the response of aluminum 6061-T651 samples under dynamic tension, and to calibrate a strength model for them. Interpretation of SHTB tests cannot be done with the so-called classical analysis, because: 1) the samples are long (relative to compression samples) and are not in dynamic equilibrium; 2) a neck is usually formed towards the end of the test; and 3) the strain to failure is quite high (around 50%). We therefore interpret the tests (calibrating from them a strength model and validating it), using computer simulations of the entire test system. Our entire system simulations are able to reproduce with good fidelity: 1) the response of the SHTB gauges on the two bars; 2) the time evolution, shape and location of the neck; and 3) the strain to failure measured after the test.